The role of stress mindsets and coping in improving the personal growth, engagement, and health of small business owners. (19th June 2022) - Paustian‐Underdahl, Samantha C.; Palmer, Joshua C.; Halliday, Cynthia Saldanha; Blass, Fred R.
Summary: The COVID‐19 pandemic has had a devastating impact on small businesses and nonprofit organizations worldwide, resulting in rising stress and worry for many small business owners. While stress is typically considered to be harmful to health and well‐being, recent work suggests that improving one's mindset about the benefits of stress can help one to respond to stress more effectively. In the current study, we use a preintervention and postintervention design and latent change score analysis to examine the impact of changing one's stress mindset on changes in personal growth, engagement, and health among small business owners—via changes in coping behaviors. Further, we examine how the perceived likelihood of needing to permanently close one's business may strengthen the effects of changing one's stress mindset on changes in approach and avoidance coping, and subsequent outcomes. In doing so, we begin to uncover the theoretical mechanisms underlying how having a stress‐is‐enhancing mindset can bring about changes in personal growth, engagement, and health. We also incorporate qualitative data to better contextualize the stress and coping‐related attitudes and behaviors of small business owners during the pandemic. This work has significant practical implications for small business owners and others experiencing work‐related stressors.